Intermittent fasting protects against food allergy in a murine model via regulating gut microbiota - Ma, Ru-xue; Hu, Jia-qian; Fu, Wei; Zhong, Jian; Cao, Can; Wang, Chang-chang; Qi, Shi-quan; Zhang, Xiao-Lian; Liu, Guang-hui; Gao, Ya-dong (Frontiers in Immunology, 2023)
Background: The prevalence of food allergy (FA) is increasing. The decrease in the diversity of gut microbiota may contribute to the pathogenesis of FA by regulating IgE production of B cells. Intermittent fasting (IF) is a popular diet with potentials of regulating glucose metabolism, boosting immune memory and optimizing gut microbiota. The potential effect of long-term IF on the prevention and treatment of FA is still unknown. Methods: Two IF protocols (16 h fasting/8 h feeding and 24 h fasting/24 h feeding) were conducted on mice for 56 days, while the control mice were free to intake food (free diet group, FrD). To construct FA model, all mice were sensitized and intragastrical challenged with ovalbumin (OVA) during the second half of IF (day 28 to day 56). Rectal temperature reduction and diarrhea were recorded to evaluate the symptoms of FA. Levels of serum IgE, IgG1, Th1/Th2 cytokines, mRNA expression of spleen T cell related transcriptional factors and cytokines were examined. H&E, immunofluorescence and toluidine blue staining were used to assess the structure changes of ileum villi. The composition and abundance of gut microbiota were analyzed by 16srRNA sequencing in cecum feces. Results: The diarrhea score and rectal temperature reduction were lower in two fasting groups compared to FrD groups. Fasting was associated with lower levels of serum OVA-sIgE, OVA-sIgG1, interleukin (IL)-4 and IL-5, and mRNA expression of IL-4, IL-5, and IL-10 in the spleen. While no significant association was observed in interferon (IFN)-γ, tumor necrosis factor (TNF)-α, IL-6, IL-2 levels. Less mast cell infiltration in ileum was observed in 16h/8h fasting group compared to FrD group. ZO-1 expression in the ileum of the two fasting groups was higher in IF mice. 24h/24h fasting reshaped the gut microbiota with the higher abundance of Alistipes and Rikenellaceae strains compared to the other groups. Conclusion: In OVA-induced mice FA model, long-term IF may attenuate FA by reducing Th2 inflammation, maintaining the integrity of intestinal epithelial barrier, and preventing gut dysbiosis.